2019
DOI: 10.1186/s12967-019-1904-5
|View full text |Cite
|
Sign up to set email alerts
|

High NCALD expression predicts poor prognosis of cytogenetic normal acute myeloid leukemia

Abstract: Background Acute myeloid leukemia (AML) is a heterogeneous disease in terms of genetic basis, clinical, biological and prognostic, and is a malignant clonal disease of leukemia stem cells (LSCs). Nearly half of adult AML patients exhibit a cytogenetic normal acute myeloid leukemia (CN-AML). The expression level of NCALD gene was associated with the prognosis of ovarian cancer and non-small cell lung cancer (NSCLC). The expression level of NCALD gene is still unclear in the prognosis of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…NCALD was related to prognosis in cancers. For instance, high expression of NCALD predicts worse survival of acute myeloid leukemia 44 . However, more studies support the opposite observation that NCALD low expression implies poor prognosis in cancer.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…NCALD was related to prognosis in cancers. For instance, high expression of NCALD predicts worse survival of acute myeloid leukemia 44 . However, more studies support the opposite observation that NCALD low expression implies poor prognosis in cancer.…”
Section: Discussionmentioning
confidence: 96%
“…NCALD encodes a cognate of bovine neurocalcin delta, 41 and expressed in many tissues, comprising normal brain, lymphoblasts, and ovarian tissue 42 . The association of NCALD with cancer was unclear until recent years when a few studies indicated its dysregulated function in prostate cancer, 43 lung cancer, 13 and normal acute myeloid leukemia 44 . We determined that NCALD expression was downregulated at the transcript and protein levels in OC specimens and drug‐resistant OC cells and specimens in contrast to controls (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…NCALD consists of four EF hand motifs, but only three can bind to calcium, which alters the conformation of the NCALD protein [10]. Studies have found that NCALD expression is associated with the prognosis of acute myeloid leukemia and non-small cell lung cancer, indicating its clinical potential as a prognosis biomarker [11,12]. In ovarian cancer, Isaksson's study showed that low expression of NCALD predicts poor prognosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ahn et al (7) reported that in patients with NK-AML, the presence of mutated chromatin, RNA-splicing genes or both was associated with poor survival. In general, these studies (3)(4)(5)(6)(7) have indicated high genetic heterogeneity in NK-AML. Patients with NK-AML exhibit marked differences in terms of prognosis (8).…”
Section: Introductionmentioning
confidence: 99%